Comparison of Delta-Shape Anastomosis and Extracorporeal Billroth I Anastomosis after Laparoscopic Distal Gastrectomy for Gastric Cancer: A Systematic Review with Meta-Analysis of Short-Term Outcomes. - Geng-Yuan Hu; Feng Tao; Ke-Wei Ji; Wei Wang (PLoS ONE)
Objective The aim of this systematic review and meta-analysis is to evaluate the safety and relative benefits of delta-shape anastomosis (DA) by comparing to conventional laparoscopy-assisted distal gastrectomy with Billroth I gastroduodenostomy (LADG BI). Methods Studies and relevant literature regarding DA versus LADG BI were searched in the electronic databases. Operation time, postoperative complications, estimated blood loss, number of retrieved lymph nodes, time to first flatus, time to oral intake, length of postoperative hospitalization in DA and LADG BI were pooled and compared using meta-analysis. Weighted mean differences (WMDs) and odds ratios (ORs) were calculated with 95% confidence intervals (CIs) to evaluate the effect of DA. Results Eight studies of 1739 patients were included in the meta-analysis. Compared with LADG BI, DA had shorter postoperative hospitalization (WMD = -0.47, 95%CI: -0.69 to -0.25, P<0.01), less blood loss (WMD = - 25.90, 95%CI: -43.11 to -8.70, P<0.01), shorter time to oral intake (WMD = -0.25, 95%CI: -0.49 to -0.01, P = 0.04), and more retrieved lymph nodes (WMD = 1.36, 95%CI: 0.30 to 2.43, P = 0.01). Operation time (WMD = -0.07, 95%CI -15.58 to 15.43, P = 0.99), overall postoperative complication rate (OR = 1.05, 95%CI: 0.74 to 1.49, P = 0.63), surgical complication rate (OR = 1.02, 95%CI: 0.70 to 1.49, P = 0.90), nonsurgical complication rate (OR = 1.21, 95%CI: 0.54 to 2.72, P = 0.64), leakage rate (OR = 2.54, 95%CI: 0.92 to 7.01, P = 0.07), stricture rate (OR = 0.36, 95%CI: 0.09 to 1.44, P = 0.15), wound complication rate (OR = 0.71, 95%CI: 0.33 to 1.55, P = 0.39), time to first flatus (WMD = -0.10, 95%CI: -0.27 to 0.07, P = 0.26), and proximal surgical margin (WMD = -0.25, 95%CI: -1.14 to 0.65, P = 0.59) was not statistically different. Conclusion Compared with LADG BI, DA is a safe and feasible procedure, with significantly reduced blood loss, time to oral intake, and postoperative hospitalization.